Dopant‐induced microstructural, optical, and electrical properties of TiO2/PVA composite. Issue 4 (27th November 2014) - Praveena, S.D.; Ravindrachary, V.; Bhajantri, R.F.; Ismayil,
Abstract : The optical, electrical, and microstructurtal properties of pure and TiO2 /Poly(vinyl alcohol) (PVA) composite polymer films were carried out using FTIR, XRD, UV‐Visible, DC electrical conductivity, and Positron annihilation lifetime spectroscopy (PALS) techniques. The FTIR study reveals that the Ti + ions of TiO2 interacts with the OH groups of PVA via intra / inter molecular hydrogen bonding and forms charge transfer complex (CTC). These formed CTC will affect the optical property of the composite film, which is reflected from UV‐Visible study. Using the observed UV–Visible spectra, optical energy band gap is estimated and its value decreases with increasing dopant concentration. The positron annihilation studies show that the considerable effect on free volume related microstructure of the PVA due to doping and complex formation. These microstructural modifications are also enhances PVA crystallinity which is reflected from XRD studies. It is also observed that the TiO2 particle forms cluster within the PVA due to the aggregation of particles and these particle cluster size increases with dopant concentration. These microstructural variations due to doping affects the DC electrical conductivity and its variations are understood based on the intra chain one‐dimensional interpolaron hopping conduction mechanism. POLYM. COMPOS. 37:987–997, 2016. © 2014 Society of Plastics Engineers